Association between rosacea and cardiovascular disease: A systematic review and meta‐analysis. (21st December 2020) - Zhang, Jiawen; Yan, Yang; Jiang, Peiyu; Liu, Zijing; Liu, Yunyi; Liu, Yixuan; Wang, Xiaoyan; Li, Min; Xu, Yang
Abstract: Background: Rosacea and cardiovascular diseases (CVD) are chronic inflammatory disorders. While CVD is the leading cause of mortality globally, increasing evidence indicates that CVD prevalence could be higher among patients with rosacea. Aims: This review aimed to determine the association between the prevalence of CVD and rosacea. Patients/Methods: A systematic review of observational studies with controls available in MEDLINE, EMBASE, PubMed, Cochrane, and Web of Science databases was conducted. We performed a pooled meta‐analysis using random‐effects weighting. Overall, 11 studies met the inclusion criteria, which indicated increased odds for at least one risk factor of CVD, including diabetes, high blood pressure, or dyslipidemia. Results: The pooled meta‐analysis indicated an association of rosacea with higher odds of insulin resistance or diabetes (odds ratio [OR], 1.18; 95% confidence interval [CI], 0.97‐1.45), high systolic blood pressure (OR, 1.96; 95% CI, 1.35‐2.84), dyslipidemia (OR, 1.50; 95% CI, 1.19‐1.88), and CVD (OR, 6.65; 95% CI, 2.80‐15.76). No publication bias was detected. The effect of confounding factors due to overlapping symptoms and lack of individual‐level data were limitations of this review. Conclusion: Patients with rosacea have a high risk of CVD. However, further studies are warranted to confirm the association between rosacea and CVD.